A place for truth : leading thinkers explore life's hardest questions - Willard, Dallas, 1935-2013.; Cho, Daniel; Park, Sarah; Veritas Forum (Downers Grove, Ill. : IVP Books, 2010)
Since its founding at Harvard in 1992, The Veritas Forum has provided a place for the university world to explore the deepest questions of truth and life. Now gathered in one volume are some of The Veritas Forum's most notable presentations. Volume editor Dallas Willard introduces each presentation, highlighting its significance and putting it in context for us today. Also included are selected question and answer sessions with the speakers from the original forum experiences. --from publisher description
Truth. Is there life after truth? / Richard John Neuhaus -- Time for truth / Os Guinness -- Reason for God : the exclusivity of truth / Timothy J. Keller -- Faith and science. The language of God : a scientist presents evidence for belief / Francis S. Collins -- The new atheists and the meaning of life / Alister McGrath, David J. Helfand -- A scientist who looked and was found / Hugh Ross -- Atheism. The psychology of atheism / Paul C. Vitz -- Nietzsche versus Jesus Christ / Dallas Willard -- Meaning and humanity. Moral mammals : does atheism or theism provide the best foundation for human worth and morality? / Peter Singer, John Hare -- Living machines : can robots become human? / Rodney Brooks, Rosalind Picard -- The sense of an ending / Jeremy S. Begbie -- Christian worldview. Simply Christian / N.T. Wright -- Social justice. Why human rights are impossible without religion / John Warwick Montgomery -- Radical Marxist, radical womanist, radical love : what Mother Teresa taught me about social justice / Mary Poplin -- The whole gospel for the whole person / Ronald J. Sider.
"Highlights from the Veritas Forum."
Includes bibliographical references.
Keywords: Theology